Procedures of domesticating culture-related words in the noble Qur’an - Ayyad, Ghada Rajeh; Tengku Sepora Tengku Mahadi (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the major problems of translating a religious text is words that are deeply rooted in the source language culture. These words have no equivalents in the target language culture which constitutes an obstacle to translators. To overcome this problem, Venuti (1995) suggested the domestication strategy to translate such words. The purpose of this paper is to discuss the translation procedures used to domesticate culture-related words in the Noble Qur’an. The study finds that the procedures used by the translators to apply the domestication strategy are: modulation, generalization, paraphrase, cultural equivalent and functional equivalent. On one hand, the paraphrase and functional equivalent procedures can be used effectively to transfer the intended meaning. On the other hand, the generalization, cultural equivalent and modulation procedures are not recommended to be used as they do not transfer the meaning in full. To use these procedures, translators need to use additional procedures such as footnotes and addition to help in clarifying and transferring the meaning in full.